Microbes as Resources to Remove PPCPs and Improve Water Quality - Francesca Demaria; Marcel Suleiman; Philippe Corvini; Pilar Junier (Microbial Biotechnology)
ABSTRACT The inadequate removal of pharmaceuticals and personal care products (PPCPs) by traditional wastewater treatment plants (WWTPs) poses a significant environmental and public health challenge. Residual PPCPs find their way into aquatic ecosystems, leading to bioaccumulation in aquatic biota, the dissemination of antibiotic resistance genes (ARGs), and contamination of both water sources and vegetables. These persistent pollutants can have negative effects on human health, ranging from antibiotic resistance development to endocrine disruption. To mitigate these risks, there is a growing interest in exploiting microorganisms and their enzymes for bioremediation purposes. By harnessing the metabolic capabilities of microbial communities, PPCPs can be efficiently degraded, transformed, or sequestered in water systems. Additionally, microbial communities exhibit remarkable adaptability and resilience to diverse PPCP contaminants, further underscoring their potential as sustainable and cost‐effective solutions for water treatment. This review explores the promise of microbial bioremediation as an approach to addressing the complex challenges posed by persistent PPCP contamination, emphasising its potential to safeguard both environmental integrity and human well‐being.